Effects of sulphur in presence and absence of farmyard manure on onion (Allium cepa) under onion-maize (Zea mays) cropping sequence - Raina, S K; Jaggi, R C (The Indian Journal of Agricultural Sciences, 2008)
Field experiment conducted during 2003-06 to study the effects of 4 (0, 15,30 and 45 kg/ha.) S levels in the absence and presence of 25 tonnce farmyard manure/ha in onion (Allium cepa L.) - maize (Zea mays L.) system. The results show the positive effects of 30 kg S/ha on bulb yield over the previous levels of 0 and 15 kg/ha (direct effect). Addition of sulphur beyond 30 kg/ha brought the yield to the level of 0 and 15 kg/ha. Application of farmyard manure @ 25 tonnes/ha significantly increased bulb and foliage yield. Sulphur-farmyard manure interaction was positive at low and negative at higher levels of S. Highest yield (yield) was observed either in treatment combination of 25 tonnes farmyard manure/ha without S or 30 kg S/ha without farmyard manure. Plant height significantly increased only by Farmyard manure (from 57.4-59.1 cm) over without farmyard manure. In maize (residual effect) and also in onion-maize sequence as a whole (direct + residual effects) the same trend was visible except that the sulphur-farmyard manure interaction was significant only in the later. Sulphur addition beyond 30 kg/ha brought down the total economic yield and also the foliage yield of both the crops to the level of either 15 kg S/ha or even control.